The Potential Role of PPPs in Developing a Sustainable SME Sector in Developing Countries: A South African Experience - Mabuza, Patrick (Journal of Economics and Behavioral Studies, 2018)
The introduction of Public-private Partnerships (PPPs) in infrastructure provision has changed the way in which governments around the world now view infrastructure provision. However, the introduction of PPPs to deliver infrastructure has not benefited the broader public. Although SMEs are important for employment creation, inequality and poverty reduction, the participation of SMEs (small and medium enterprises) in PPP projects is very low in developing countries. This is because PPP models in developing countries are developed based on those used in developed economies, and such models ignore the socioeconomic realities facing developing countries. The objective of this study is therefore to demonstrate that PPP projects in developing countries present an opportunity for growing the SME sector and create the needed jobs and contribute to poverty alleviation. The study has found that PPP projects have the potential to develop a sustainable SME sector, as it has found that SMEs do participate in PPP projects; however, their participation is curtailed by a number of challenges such as: lack of access to finance, limited human resources, low technological capabilities, and lack of access to markets. It also found that linking SMEs to PPP projects may address some of these challenges to a certain extent, especially if SMEs provide services to PPP projects during both the implementation and the operational phases of PPP projects. It also found that PPPs have not yet been identified by the South African government as one of the initiatives that can facilitate SME development. Most focus on PPP projects is only on ensuring that they include ownership by previously disadvantaged South Africans. The study recommends that a policy be developed that will incentivise PPP firms to use SMEs in their projects and penalise those PPP firms that fail to comply with the policy imperatives. It went on and found that the different South African government institutional initiatives or frameworks to support SMEs seem to be adequate; however, what is needed is a cohesive approach that links all these initiatives together and ensures that they support one another.